Ultrasonic characterisation of the binary mixture of 2, 3-dichloroaniline with methanol and ethanol. Issue 4 (8th August 2022) - Kumar, Mahendra; Khan, Mohd Aftab; Yadav, Chandreshvar Prasad; Pandey, Dharmendra Kumar; Singh, Dhananjay
ABSTRACT: The present work focuses on the ultrasonic characterisation of the binary mixture having constituent liquids, 2, 3-dichloroaniline and methanol/ethanol, by measuring their density, viscosity, ultrasonic velocity and estimating thermo-physical parameters at 25°C. The density, viscosity, ultrasonic velocity, acoustic impedance and relative association decay, while compressibility and free length increase with the increase in mole fraction of solvent in the present binary mixture. An anomalous change is received in excess molar volume, free volume, thermal relaxation time, Gibbs free energy and ultrasonic absorption up to 80% solvent mole fraction. The analysis reveals that the binary mixture 2, 3-DCA+ methanol has a good intermolecular interaction strength, and is more structural and less corrosive than 2, 3-DCA+ ethanol due to the formation of excess hydrogen bonding at 70% solvent mole fraction. GRAPHICAL ABSTRACT: UF0001